1986
DOI: 10.1007/bf02906837
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome pairing and chiasma formation in allohexaploid wheat, Triticum aestivum analyzed by spreading of meiotic nuclei

Abstract: An ultrastructural analysis of spread, silver stained meiotic nuclei of wheat, Triticum aestivum, has been performed. Partial tracings of lateral components and synaptonemal complexes of a number ofleptotene and early zygotene nuclei, and complete tracings of eleven mid zygotene, seven late zygotene, twenty pachytene, twelve early diplotene, twenty-one mid diplotene and sixteen late diplotene nuclei have permitted the following observations and conclusions: 1) The chromosomes appear to be randomly distributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
94
0
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 133 publications
(104 citation statements)
references
References 65 publications
9
94
0
1
Order By: Relevance
“…The materials, the growth conditions and the procedures for light and electron microscopy are described in the individual reports in this series (18,20,21,22,23,30,79,80,84).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The materials, the growth conditions and the procedures for light and electron microscopy are described in the individual reports in this series (18,20,21,22,23,30,79,80,84).…”
Section: Methodsmentioning
confidence: 99%
“…Ultrastructural studies ofeuploid wheat using serial sectioning and three dimensional reconstruction (18,30) or spreading and silver staining of meiotic nuclei (20) revealed that chromosome pairing and synaptonemal complex formation at zygotene primarily occurred between homologues. However, in most nuclei (8 of 11 mid zygotene and 4 of 7 late zygotene nuclei (20)) one or more multiple associations had formed due to pairing partner exchanges.…”
Section: Introduci'ionmentioning
confidence: 99%
See 3 more Smart Citations